Pilgrim flasks: chronological and cultural transformations from the New Kingdom to the Napatan period - Kilroe, L (2019)
Ceramic pilgrim flasks were prevalent across the Eastern Mediterranean during the Late Bronze and Early Iron Age, and were adopted into Egypt during the reign of Thuthmosis III. Their changing synchronic and diachronic usage across these contexts has however been little explored, and research demonstrates their integral position in commodity exchange. This approach sheds light on how Egyptian colonial practices in New Kingdom and Post New Kingdom Nubia affected material culture. During the course of this study, I applied typological and anthropological methodologies to pilgrim flasks to examine how vessel use changed across this cultural border, and the disparate ways this can be represented in the archaeological record. I collated 1635 pilgrim flasks from across Egypt and Nubia to approach three research questions: 1. How does pilgrim flask morphology change as it moves across the cultural landscape between Egypt and Nubia? 2. How were pilgrim flasks used? Do the deposition patterns of flasks suggest shifting usage between the New Kingdom (c. 1550–1070 BCE) and the Early Napatan (c. 700– 500 BCE) in these regions? 3. What can these vessels ultimately reveal about cultural practices in Nubia, both before and after the withdrawal of the Egyptian colonial control at the end of the New Kingdom? I developed new typologies for Egypt and Nubia to compare the different morphological and distribution patterns visible. This revealed distinct regional practices associated with the form. The application of Practice models to the data scrutinised the divergent meanings associated with the vessel across these traditions, which were associated with both wine and perfumed oils in Egypt, but libation practices in Nubia. Pilgrim flasks were affected by colonial practices in Nubia and were swiftly appropriated into new habitus traditions. Their use in mixed colonial towns contributed to the ethnogenesis of an urban habitus that inspired institutions in the Early Napatan state.